Quantitative Assessment of structural reforms : modeling the lisbon strategy - Arpaia, Alfonso; Roeger, Werner; Varga, Janos; Veld, Jan in't 1962-; Grilo, Isabel; Wobst, Peter; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
Using a variety of economic models, the Commission services have examined the impact of several reforms forming part of the Growth and Jobs Strategy (GJS). Overall, the results show that past reforms have delivered significant benefits, and that further reforms in key areas could generate important additional gains. The modelling results provide support for the existence of positive interactions between structural reforms in different areas, and thus for having a comprehensive reform strategy. They also highlight spillovers between reforms at EU and national level, the magnitude of which is being enhanced through the growing intensity of trade and investment.
Economic Papers